Endemic taxon or environmentally induced colour morph? Genetic insights into the insular subspecies of Platyceps najadum (Serpentes, Colubridae) from Kalymnos, Greece - Daniel Jablonski; Elias Tzoras (ZooKeys, 2025)
Phenotypic variation, particularly in colouration, is well documented in snake populations across the Balkans, with insular populations often exhibiting distinct morphological traits. Historically, these differences have been used to define subspecies or even new species. However, many such classifications have been revised following genetic analysis. One unresolved taxonomic case involves the subspecies Platyceps najadum kalymnensis (Schneider, 1979), a melanistic taxon endemic to Kalymnos Island, Greece. In this study, we present the first genetic data (both mitochondrial and nuclear) for P. n. kalymnensis, comparing it with populations from the Balkan–Anatolian range to clarify its evolutionary status. Mitochondrial DNA analysis reveales that P. n. kalymnensis clusters closely with the Balkan and Anatolian populations, exhibiting low levels of genetic differentiation. However, nuclear markers reveal distinct allelic variations, suggesting a degree of evolutionary independence, likely influenced by the island’s long-term specific environmental conditions. Our results support the continued recognition of P. n. kalymnensis as a distinct subspecies, though further studies using high-resolution genomic data are needed to better understand its evolutionary trajectory.